The Significance of Developing Advanced Higher Order Thinking Skills in China’s Arts Education - Yang Yang; Yee Mei Heong (Journal of TVET and Technology Review, 2024)
Arts education has an integrative role in promoting the intellectual, aesthetic and emotional growth of students. Arts education not only develops students’ professional skills, but also helps them develop holistically. To achieve good results in the arts, students need to be innovative. In China, arts education has been innovating, however, challenges remain, including the use of standardized testing, gaps in educational resources, and teacher pedagogy, all of which affect the development of students’ innovative abilities. Higher order thinking skills (HOTS) play a key role in students’ academic success and innovation; HOTS encourages critical analysis, fosters creative problem-solving skills, and prompts innovative thinking, which helps art students to improve their thinking skills and develop their creative abilities. Currently, there is a lack of consensus and widespread application of HOTS in Chinese art programs. the integration of HOTS with arts education becomes crucial in ensuring students’ cognitive development as they cope with the challenges posed by social development.